(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study presents the results of scientific research conducted to evaluate the effectiveness of weight management strategies through comprehensive measures for healthy nutrition and adequate physical activity under military service conditions.